Sarthaks Test
0 votes
92 views
in Mathematics by (15.0k points)

Find and correct the errors in the statement: 

(y − 3)2 = y2 − 9

1 Answer

0 votes
by (24.8k points)
selected by
 
Best answer

L.H.S = (y − 3)2 = (y)2 − 2(y)(3) + (3)2  [(a − b)2 = a2 − 2ab + b2]  = y2 − 6y + 9 ≠ R.H.S

The correct statement is (y − 3)2 = y2 − 6y + 9

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...